MAKETÉKAN TRADISI CACAH JIWA SAKRAL DI DESA PAKRAMAN PATAS, TARO. - I Komang Aryadi Arnata (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
In an effort to realize the goal of Hindus, namely moksartham Jagadhita ya ca iti dharma, there are so many ways and means that can be achieved according to abilities and traditions that are passed down both orally and in writing. In connection with this, the implementation of the Maketékan tradition in Desa Pakraman Patas Taro is carried out every tilem sasih kanem. Interestingly, the implementation of the Maketékan tradition has its own uniqueness in which there is a very thick function and meaning. The uniqueness is seen in the facilities used in the implementation process such as képéng money (pis bolong) and there are differences in the vows paid between male and female residents. In addition, the uniqueness of the ceremony, namely the implementation of this tradition is carried out at Pura Dalem and the képéng money deposited is believed to be a safety talisman for family members. On this basis, it is very interesting to study this in the following scientific paper so that it can find the functions and values in the implementation of the Maketékan tradition in the Pakraman Village of Patas Taro.